CHARACTERISTICS OF CARAGENAN FROM RED SEAWEED (RHODOPHYTA) Eucheuma spinosum AND Eucheuma cottonii ORIGINATING FROM MORO ISLAND - Ika Darmila Siregar; Andarini Diharmi; Rahman Karnila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Red seaweeds Eucheuma spinosum and E. cottonii are raw materials for producing carrageenan. Carrageenan is a group of polysaccharides widely used as thickening, stabilizing, and gelling agents across various industries. This study aims to determine the physicochemical characteristics of carrageenan from E. spinosum and E.cottonii seaweed. This research uses an experimental method: direct extraction with hot alkali, with three repetitions. The physicochemical parameters analyzed include yield, gel strength, viscosity, water content, ash content, and sulfate content. The results of the study of the physicochemical characteristics of carrageenan from E. spinosum raw materials produced a yield of 34.41%, gel strength 22.17 g/cm2, viscosity 1450 cP, water content 11.57%, ash content 24.41%, and sulfate content 24.89%. The results of the study of the physico-chemical characteristics of E. cottonii produced a yield of 29.54%, gel strength of 488.58 g/cm2, viscosity of 30.05 cP, water content of 9.95%, ash of 36.42%, and sulfate content of 21.42%. The FTIR profiles of E. spinosum carrageenan compounds show iota carrageenan, and those of E. cottonii carrageenan compounds show kappa carrageenan. The physicochemical characteristics of E. spinosum and E.cottonii carrageenan raw materials have met FAO standards, except for gel strength and ash content in E. cottonii carrageenan.